Profitability, Inventory Intensity and Corporate Tax Avoidance in Nigeria : The Moderating Effect of Institutional Ownership - Ahmad Haruna, Abubakar; Azam Abdelhakeem, Khalid Ahmed; Rossazana, Ab Rahim; Znar Nahro, Ahmed (Malaysian Finance Association, 2024)
Research Question: This paper examines whether the presence of institutional investors can moderate the association between profitability on corporate tax avoidance. Motivation: The motivation behind this study is that corporate tax avoidance practices have become a major concern for the government globally because it’s negatively affects revenue generation. Similarly in Nigeria, despite the tax law reform which aims to eliminate unclear and conflicting element in the tax provision, tax avoidance activities continue to occur. Such can be seen from the recent cases of Multichoice, MRS and Chevron. Idea: The core idea of this research is to examine the moderating role of institutional investors on the relationship between profitability and corporate tax avoidance. Data: Data for this study were obtained from the financial statement of the listed firms in Nigeria, accessed through Thompson Reuters DataStream, as well as from their annual reports for five years (2018-2022). Method/Tools: Panel Corrected Standard Error is employed to analyse the data. Findings: The results reveal that despite the negative effect of profitability on effective tax rate, the presence of institutional investors would provide efficient monitoring and reduce tax fraud and manipulation in the firm. Also, the results indicate that high inventory intensity in a company is linked to the significant cost of goods sold, leading to reduced profits. Consequently, lower profits result in lower company taxes, which in turn reduces the effective tax rate. Contributions: Therefore, the study provide evidence to support the long-term institutional investors have the knowledge, capability, and resources to inspect managers and exercise control on them. Also, the results of this study will also provide the Nigerian tax authority with useful information and empirical support, the Federal Inland Revenue Service (FIRS) should put in place strict measures to reduce aggressive use of tax planning strategies by firms. Hence, future studies could study how shift in tax policies, tax enforcement, or corporate tax incentives in Nigeria impact tax avoidance practices among firms in Nigeria. Also, future studies could analyse how institutional investors in Nigeria respond to regulatory changes and whether such changes alter the extent of tax avoidance practices.